2015
DOI: 10.1002/iroh.201401784
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology of the invasive Amur sleeper (Perccottus glenii Dybowski, 1877) in Central Europe

Abstract: 27In the last two decades, the invasion of the Amur sleeper (Perccottus glenii Dybowski, 1877) 28 originating from the Far East can be observed in Eastern and Central Europe. Since the Amur 29 sleeper is a non-game fish species, few detailed studies exist on its feeding ecology both in its 30 native and invaded habitats. We examined the seasonal feeding ecology of Amur sleeper in a 31 lentic and in a lotic habitat. Chironomid larvae, zygpoteran larvae, crustaceans and 32 ephemeropteran larvae dominated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The ongoing species invasion is probably the outcome of deliberate and non-deliberate stocking, which is thought to be facilitated by P. glenii opportunism, flexible life-history characteristics, and aggressive behaviour as well as by its ability to survive in degraded environmental conditions (Ćaleta et al, 2011;Reshetnikov and Ficetola, 2011). The ability of P. glenii to effectively use trophic resources ranging from ciliates to vertebrates (Reshetnikov, 2003;Ko sčo et al, 2008;Grabowska et al, 2009;Kati et al, 2015) coupled with the prolonged reproductive period allows the coexistence of individuals of multiple sizes. The species is able to escape competition and predation by inhabiting water bodies unsuitable for most other freshwater fishes in Northern Europe.…”
Section: Introductionmentioning
confidence: 99%
“…The ongoing species invasion is probably the outcome of deliberate and non-deliberate stocking, which is thought to be facilitated by P. glenii opportunism, flexible life-history characteristics, and aggressive behaviour as well as by its ability to survive in degraded environmental conditions (Ćaleta et al, 2011;Reshetnikov and Ficetola, 2011). The ability of P. glenii to effectively use trophic resources ranging from ciliates to vertebrates (Reshetnikov, 2003;Ko sčo et al, 2008;Grabowska et al, 2009;Kati et al, 2015) coupled with the prolonged reproductive period allows the coexistence of individuals of multiple sizes. The species is able to escape competition and predation by inhabiting water bodies unsuitable for most other freshwater fishes in Northern Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Trophic plasticity is a fundamental condition for species to adapt to a newly created lentic environment such as the reservoirs. Introduced species can affect the functioning of ecosystems by changing trophic relationships, besides presenting other deleterious effects (Adams 1991, Meffe et al 1997, Marchetti 1999, Kati et al 2015. These changes may have important economic and ecological consequences (Gomiero & Braga 2003, Fugi et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These changes may have important economic and ecological consequences (Gomiero & Braga 2003, Fugi et al 2008). Native species may change their abundance due to competition with non-native species (Zaret & Paine 1973, Lodge 1993, Khan & Panikkar 2009, Kati et al 2015. On the other hand, non-native species can alter the functioning of local ecosystems by intensifying predation pressure on native species, or by searching for other prey that are not used by native predators (Zavaleta et al 2001, Laxson et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…The success of an alien invasive species depends on its high environmental tolerance and its life-history traits (Grabowska and Przybylski 2015). Therefore, in order to conserve the biodiversity, it is very important to investigate the ecology of invasive species (Erős 2005, Grabowska et al 2011, Grabowska and Przybylski 2015, Kati et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Amur sleeper is a very effective predator of a wide range of aquatic animal species at all trophic levels. It mainly consumes macroinvertebrates, eggs, and even larvae and juveniles of fishes and amphibians (Reshetnikov 2003, Koščo et al 2008, Grabowska et al 2009, Kati et al 2015. Many studies have reported a negative correlation between the abundance of P. glenii and that of native fishes (e.g., Rešetnikov 2001, Reshetnikov 2003, Koščo et al 2003a.…”
Section: Introductionmentioning
confidence: 99%